Phytochemical Screening And Separation Of Various Extracts Of Cyanobacterium Nostoc Muscorum (International Journal of Food and Nutritional Sciences, 2022)
Cyanobacteria is a free-living microorganism surviving in both terrestrial and fresh water habitat. Various strain of cyanobacteria is well known for the production of intracellular and extracellular metabolites like antimycobacterial, antifungal, antiviral and antialgal activity. In the present study, we performed phytochemical screening of Cyanobacteria Nostoc muscorum to extract and found the presence of alkaloids, flavonoids, saponins, and glycosides; and thin layer chromatography (TLC) of cyanobacteria Nostoc muscorum. Afterward, Thin layer chromatography of extract obtained by using different solvents of non-diazotrophically and diazotrophically grown culture of the Cyanobacterium Nostoc muscorum were performed.